View of the exterior walls of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The south side elevation of the exterior walls of the Bhandasar Temple and the side shrine from the temple complex. A high plinth supports the exterior walls of the temple. The plinth details of slender fluted pilasters on the corner are characteristic of Mughal period architecture.